Islamic Intellectual Development during the Abbasid Dynasty (750 AD-861 AD) - Hasanah, Uswatun (El Tarikh : Journal of History, Culture and Islamic Civilization, 2022)
This article analyzes the history of Islamic intellectual progress during the Abbasid Dynasty which in Islamic literature is said to be the city of Baghdad as the center of Islamic civilization. In the Abbasid period, not only the Arabs filled the dynamics of Arab life, but also the Indians, Africans, Europeans, Persians, Chinese so as to form a cosmopolitical society, open, and easily accept new things that were considered useful.The dispute with the civilization of other nations brought a new influence so that science developed rapidly. In addition, the main influence is the leadership pattern of the caliphs who can provide progressive and revolutionary policies, namely providing support for the movement to translate foreign manuscripts, providing facilities for science lovers by establishing many libraries, especially Bayt al-Hikmah as an institution of education and science studies and as a library so that Muslim intellectuals are born.Key words: Abbasid Dynasty, Islamic Intellectuals